Smartphone with optical, physical, and electrochemical nanobiosensors - Seo, Sung Eun; Tabei, Fatemehsadat; Park, Seon Joo; Askarian, Behnam; Kim, Kyung Ho; Moallem, Golanz; Chong, Jo Woon; Kwon, Oh Seok (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
We reviews nanobiosensors combined with smartphone for the extended functions with optical, physical and electrochemical detection owing to the various advantages of smartphone: portable memory storage, a light source, electrical boards and power supply which are leading to an all-in-one sensing system. In this review, we introduce various nanobiosensors and their integration with smartphones. Moreover, an excellent demonstration of smartphone-based nanobiosensors is presented in each chapter with methodologies. [Display omitted] Advancement in nanoscience technology has presented various sensing platform, and the development of biotechnology has found bioprobes for disease diagnostics, leading to nanobiosensors. Although they show high sensitivity and excellent selectivity for target molecules, the nanobiosensors still need additional instruments for consumers in the field. To enable point-of-care testing (POCT) with nanobiosensors, smart devices, consisting of portable memory storage, a light source, electrical boards, a battery and so on, have been combined with nanobiosensors. Smartphone-based nanobiosensors showed extended functions with optical, physical and electrochemical modulators, leading to an all-in-one sensing system. In this review, we introduce various nanobiosensors and their integration with smartphones. Moreover, an excellent demonstration of smartphone-based nanobiosensors is presented in each chapter with several subjects: (i) optical, (ii) physical and (iii) electrochemical nanobiosensors on smartphones.